2021
DOI: 10.1111/cod.13825
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic hair extensions causing irritant contact dermatitis in patients with a history of atopy: A report of 10 cases

Abstract: BackgroundWe present a case series of 10, atopic, African women who developed irritant contact dermatitis (ICD) from synthetic hair extensions.MethodsTen consecutive African female patients who presented with a pruritic cutaneous eruption on the neck over a period of 2 years are described. Patients underwent skin patch testing using both standard and hair commercial patch test panels and samples of their own hair extensions. Hair care products were not tested.ResultsAll 10 patients used synthetic hair extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Patients presenting with sudden eruption of a rash restricted to areas of glue adhesive application should raise concern for allergic contact dermatitis. Synthetic hair fibers have also been linked to allergic dermatitis 16 . This can manifest as a pruritic eczematous rash localized to areas of contact such as the nape or any location with contact to the free end of the hair fibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients presenting with sudden eruption of a rash restricted to areas of glue adhesive application should raise concern for allergic contact dermatitis. Synthetic hair fibers have also been linked to allergic dermatitis 16 . This can manifest as a pruritic eczematous rash localized to areas of contact such as the nape or any location with contact to the free end of the hair fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic hair fibers have also been linked to allergic dermatitis. 16 This can manifest as a pruritic eczematous rash localized to areas of contact such as the nape or any location with contact to the free end of the hair fibers. If a prosthesis must be applied via glue, a water-soluble glue would be a safer option.…”
Section: Cons Of Prostheses: Traction Alopeciamentioning
confidence: 99%
“… 5 Additionally, some patients may develop contact dermatitis to the material composition of synthetic weaves. 12 …”
Section: Popular Hair Camouflage Practices In Skin Of Colormentioning
confidence: 99%
“… 32 Patients should be made aware of the potential for irritant contact dermatitis with synthetic hair. 12 Studies have shown Black patients are significantly more sensitized to para-phenylenediamine (PPD), a chemical found in hair dyes, compared to White patients. 12 PPD is the most common allergen in hair dye, with darker-colored dyes containing higher levels of PPD.…”
Section: Alopecia and Considerations For Hair Camouflage In Skin Of C...mentioning
confidence: 99%
See 1 more Smart Citation